HUBUNGAN ANTARA LOCUS OF CONTROL EKSTERNAL DENGAN KEMATANGAN KARIER DITINJAU DARI JENIS KELAMIN SISWA - Wahyuni, Alvina; Wibowo, Satrio Budi; Mudaim, Mudaim (Universitas Muhammadiyah Metro, 2025)
The aim of this research is to determine the relationship between external locus of control and career maturity in terms of gender of students at SMK Muhammadiyah 2 Metro. This type of research is quantitative correlational research. The data obtained from the results of this research is the correlation between External Locus of control and Career Maturity and gender. It is stated that there is a significant relationship between external locus of control and career maturity in students at SMK Muhammadiyah 2 Metro with the most influential indicator being the influence of other people. and the lowest indicator is fate. Meanwhile, gender has no relationship with career maturity, nor does external locus of control have a relationship with gender in class XII students at SMK Muhammadiyah 2 Metro.